-6-7=-13 because you take -2 and 3 you multiply equals-6 than add -7 and it well give you your answer
40 + 30s = 220
30 for each student (s) and the one charge of 40 would get the tutor 220 dollars.
<h3><u>given</u><u>:</u></h3>
<u>
</u>
<h3><u>solution</u><u>:</u></h3>
<u>
</u>
<u>
</u>
<u>
</u>
Answer:
28/3
Step-by-step explanation:
Answer:
Step-by-step explanation:
f * g = (x^2 + 3x - 4) (x+4)
open bracket
x((x^2 + 3x - 4) + 4 (x^2 + 3x - 4)
x³ +3x²-4x+x²+12x-16
x³+3x²+x²-4x+12x-16
x³+4x²+8x-16 (domain is all real numbers.
f/g = (x^2 + 3x - 4)/(x+4)
factorising (x^2 + 3x - 4)
x²+4x-x_4
x(x+4) -1 (x+4)
(x+4)(x-1)
f/g = (x^2 + 3x - 4)/(x+4) =(x+4)(x-1)/(x+4) = (x-1)
Before factorisation, this was a rational function so the domain is all real numbers excluding any value that would make the denominator equal zero.
Hence I got x - 1, and x cannot equal -4
So the domain is just all real numbers without -4